Optimization of process parameters in fabricating AA6082/Nip surface composite using friction stir processing technique - Santhoshkumar S; Senthil Kumar K L; Kalil Rahiman M; Manojkumar S (Materials Research Express)
In this present study, an attempt was made to improve the Ultimate Tensile Strength (UTS) and Microhardness (MH) of friction stir-processed AA 6082 with Ni _p surface composites without affecting the ductility of the Base Metal (BM). Ni _p micron particle with an average size of 149 μm (99.99 purity) was utilized as reinforcement and AA6082 as a matrix for fabricating the surface composites. Process parameters namely rotational speed, transverse speed, and volume fraction with three levels considered as input parameters for this study. Moreover, ultimate tensile strength, microhardness, and wear rate were determined as process output. For this study, experiments were conducted as per Taguchi’s L _9 orthogonal array (OA) by repeating each trial three times and the average values were used for further analysis. ANOVA was performed to ensure the influential process parameter and the results exhibited that the volume fraction of Ni _p exhibited the most influential parameter among the three process parameters. Additionally, Grey relational analysis (GRA) was used to grade the rank of the experimental samples using the Grey Relation Coefficient (GRC). Based on this method, the optimal process parameters (Rotational Speed = 1250 rpm, Transverse Speed = 40 mm min ^−1 , Volume Fraction = 18%) were chosen and the optimal sample (Rank 1) attained a UTS of 247 MPa and MH of 100 HV. The results revealed that the fabricated composite (AA6082/Ni _p ) demonstrated an improvement in UTS (26.02%), MH (56.25%), and wear rate (57.38%) as compared to BM (AA6082). Eventually, the surfaces of the optimized samples were also analyzed by x-ray diffraction (XRD), energy dispersive x-ray analysis (EDAX), and field emission-scanning electron microscopy (FE-SEM) methods to confirm the composition of surface composite and the uniform distribution of particles.